Stability and aggregation of silver and titanium dioxide nanoparticles in seawater: Role of salinity and dissolved organic carbon. (12th March 2014) - Wang, Huanhua; Burgess, Robert M.; Cantwell, Mark G.; Portis, Lisa M.; Perron, Monique M.; Wu, Fengchang; Ho, Kay T.
Abstract The behavior and fate of nanoparticles (NPs) in the marine environment are largely unknown and potentially have important environmental and human health implications. The aggregation and fate of NPs in the marine environment are greatly influenced by their interactions with seawater and dissolved organic carbon (DOC). In the present study, the stability and aggregation of 30‐nm–diameter silver nanoparticles (AgNPs) capped with citrate and polyvinylpyrrolidone (PVP; AgNP‐citrate and AgNP‐PVP) and 21‐nm‐diameter titanium dioxide (TiO2) NPs as affected by seawater salinity and DOC were investigated by measuring hydrodynamic diameters and zeta potentials. The added DOC (in humic acid form) stabilized the 3 types of NPs when the seawater salinities were ≤5 parts per thousand (ppt), but the stabilizing effect of DOC was reduced by a higher salinity (e.g., 30 ppt). In addition, AgNP‐PVP was more stable than AgNP‐citrate in seawater, indicating that surface capping agents and stabilization mechanisms govern the stability and aggregation of NPs. Statistical analysis showed that salinity is the most dominant influence on the stability and aggregation of AgNPs and TiO2NPs, followed by DOC. These findings expand our knowledge on the behavior of AgNPs and TiO2NPs in seawater and indicate that the fate of these NPs will be primarily to aggregate in the water column, precipitate, and accumulate in sediments following release into the marine environment. Environ Toxicol Chem 2014;33:1023–1029. © 2014 SETAC